Climate Change Mitigation in the Arfak Mountains through Igya Ser Hanjob: A Legal and Socioecological Review - Pandori, Musa; Roberth KR Hammar; Christina Samangun (Manunggal Halim Jaya, 2025)
Using a juridical and socioecological approach, this study examines the role of the Igya Ser Hanjob customary legal system in mitigating climate change in the Arfak Mountains, West Papua. Igya Ser Hanjob, which literally means